Legal and Human Rights Review on The Policy Of Banning The Import Of Used Clothing - Sobari, Ahmad; Daming, Saharuddin; Ratnawaty, Latifah (Universitas Ibn Khaldun Bogor, 2024)
This study delves into the prohibition of importing second-hand clothing in Bogor City by the government based on Law No.7/2014 on Trade and Minister of Trade Regulation No. 51/M-DAG/7/2015. This ban aims to protect public health, support domestic industries, and reduce environmental impact. However, the implementation of this policy faces several challenges, including the inability of relevant agencies to monitor and crack down on imported second-hand clothing traders in Pasar Anyar Bogor. Factors such as limited authority, lack of coordination among agencies, and a societal culture that glorifies imported goods hinder the enforcement of the ban on imported second-hand clothing. Despite the numerous benefits of the ban, such as safeguarding public health and supporting local industries, its implementation is obstructed by various inhibiting factors. Therefore, enhanced supervision, law enforcement, market diversification, and international cooperation are necessary to improve the effectiveness of the ban on imported second-hand clothing policy to benefit public health, domestic industries, and environmental sustainability